2020
DOI: 10.3390/ma14010129
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Fracture Parameters of Concrete

Abstract: This study aimed to determine the influence of the volume fraction of steel fibers on the fracture parameters of concrete. Fifty notched steel-fiber-reinforced concrete (SFRC) beams and ordinary concrete beams with 100 mm × 100 mm × 515 mm were cast and tested via a three-point bending test. Among them, the type of steel fiber was the milling type (MF), and the volume fraction of steel fiber added was 0%, 0.5%, 1%, 1.5% and 2%, respectively. The effects of the steel fiber volume fraction (VF) on the critical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…When the CMOD of specimens exceeded about 0.2 mm, the load of the ASFRC specimen was still growing while the load of the SFRC specimen began to fall after the initial crack of the matrix. Specifically, the CMOD corresponding to the ultimate load of SFRC was generally not above 0.2 mm, which was also reported by Wang et al [35]. However, although the pre-initial crack behavior of ASFRC was similar with SFRC, the ASFRC specimen could still bear higher load until the peak load.…”
Section: Load-cmod Curvessupporting
confidence: 73%
“…When the CMOD of specimens exceeded about 0.2 mm, the load of the ASFRC specimen was still growing while the load of the SFRC specimen began to fall after the initial crack of the matrix. Specifically, the CMOD corresponding to the ultimate load of SFRC was generally not above 0.2 mm, which was also reported by Wang et al [35]. However, although the pre-initial crack behavior of ASFRC was similar with SFRC, the ASFRC specimen could still bear higher load until the peak load.…”
Section: Load-cmod Curvessupporting
confidence: 73%
“…Scanning electronic microscopy results indicate that polypropylene fibers restrict the propagation of cracks, which improves the strength and durability of concrete [ 6 ]. Wang et al reported that with the increase in the steel fiber volume fraction, some fracture parameters increase gradually and maintain a certain linear growth [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results revealed a compressive strength of 40.6 MPa and a tensile strength of 12.6 MPa for the thinned epoxy material post-solidification, and infrared spectra analysis indicated an enhancement in the toughness of the epoxy material due to the inclusion of the diluent. Zhang et al [20] examined four common grouting materials-ordinary silicate cement, epoxy resin, ultrafine cement, and polyurethane-and conducted comprehensive analyses, considering factors such as grouting pressure and concrete crack aperture. They investigated the anti-seepage performance of each material on concrete cracks.…”
Section: Introductionmentioning
confidence: 99%